Ru’yā and Dream Interpretation: A Comparative Analysis of Islamic Tradition and Western Psychological Perspectives - Arroisi, Jarman; Rahmawati, Aisyah; Rezkyanta, Haqiqul (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to compare Western psychological interpretations of dreams with Islamic perspectives, particularly in Qur'anic exegesis and prophetic traditions. While Western theories, such as those of Sigmund Freud and Carl Jung, conceptualize dreams as manifestations of subconscious desires or archetypal imagery, contemporary neuroscience explains them as cognitive processes during sleep. In contrast, Islamic thought considers dreams as potential channels of divine communication, offering guidance or premonitions. This research employs a descriptive qualitative method through a literature review of psychological theories, Islamic tafsir, and hadith collections. The findings reveal that while Western perspectives emphasize psychological and neurological mechanisms, the Islamic framework views dreams as a metaphysical bridge between humans and the divine. The study concludes that dreams are multidimensional experiences integrating cognitive, emotional, and spiritual dimensions. Theoretically, this research enriches the discourse on the intersection of psychology and spirituality, offering a more comprehensive understanding of dreams beyond their neuropsychological basis.